Tethered Cord Syndrome in Patient with Lipomyelomeningocele: A Case Study - I Gusti Ayu Sri Mahendra Dewi; Ni Putu Sriwidyani; Desak Made Cittarasmi Saraswati Seputra (National Cancer Center - Dharmais Cancer Hospital, 2022)
Introduction: Tethered Cord Syndrome (TCS) is a condition that occurs due to spinal cord traction caused by the attachment of the spinal cord to the surrounding tissues. The incidence of TCS is quite rare, approximately 0.25 per 1,000 live births Case Presentation: We reported a 4-year-old female patient with a lump on her sacral region since birth which enlarged over time. The patient experienced intermittent fever for 1 month before hospital admission and constipation since infancy. Physical examination revealed a lump with a diameter of 6 cm on her sacral region with no neurological abnormality. Ultrasonography examination showed an anechoic lesion with multiple linear structures on supragluteal sinistra with a size of 2.2 x 2.5 x 2.1 cm. MSCT findings showed spina bifida at L5 until S2 level with features of lipomyelomeningocele and tethered cord started from L2 level. Bilateral hydronephrosis, hydroureter, and distended bladder (pine tree appearance) with the possibility of the neurogenic bladder were also found on MSCT examination. The patient underwent surgery to excise the lump and to release the tethered cord. Microscopic findings from excised mass showed a group of neuronal and glial cells, the syncytial sheet pattern of meningothelial cells, and foci of calcification which supported lipomyelomeningocele diagnosis. Conclusions: : Intensive follow-up care and observation must be carried out in children with spinal dysraphism because it may be associated with TCS which may be asymptomatic at an early stage.